MD&A Similarity with Local Industry Peers - Wang, Yiding (My University, 2021)
This study investigates the impact of interacted industry peer firms on management decisions regarding Management Discussion and Analysis (MD&A). Given that geographic industry clusters facilitate inter-organization interactions among its participants, I examine and find that industry peer firms from the same geographic industry clusters adopt more similar MD&A disclosures, and inter-firm social networks function as a channel that facilitates MD&A similarity among these interacted industry peers. In addition, the results suggest that MD&A similarity among local industry peers is moderated by market environments and varies among different types of firms. The further analyses show after firms relocate, their MD&As become more similar to those issued by the industry peers located in the new clusters, and firms contain more similar forward-looking MD&A disclosures with the industry peers from the same geographic industry clusters. The findings are consistent with the idea that interacted industry peer firms influence individual firms’ MD&A disclosure strategies. Finally, I provide initial evidence that MD&A similarity among industry peers is informative and is a desired attribute. Overall, this study advances our understanding of how managers prepare MD&A disclosure by exploring the convergence of MD&As among industry peers, and it extends the literature on voluntary disclosure and provides new insights on peer firm effects.
Keywords: MD&A; Financial disclosure; Textual analysis